INFLUENCE OF ULTRASOUND ON NITRIC ACID LEACHING OF ALUMINA FROM KAOLIN CLAYS. (Лучшие интеллектуальные исследования, 2025)
Abstract: This article presents the results of a comprehensive study on the application of ultrasound to intensify the nitric acid leaching of alumina from calcined kaolin clays of the Angren deposit. The propagation of ultrasonic waves in liquid media induces cavitation phenomena that enhance mass transfer and reaction kinetics, especially at the solid–liquid interface. A specially designed ultrasonic bath equipped with a PMS-6M magnetostrictive transducer powered by a UZG-2.5A generator was used to investigate process intensification under controlled conditions. The experiments were conducted using a statistical design of experiments (DoE), specifically a fractional factorial design (2⁴⁻¹), to assess the influence of key parameters: temperature, leaching time, stoichiometric acid dosage, and nitric acid concentration. The optimization criterion was the yield of Al₂O₃ in solution. A regression model was developed, and the method of steepest ascent was applied to identify optimal process conditions. At the optimal point, alumina recovery reached 93% within a significantly reduced leaching time.